Decision-making Styles of Young-adult Consumers in the Republic of Macedonia - Anić I.D.; Ciunova shuleska, Anita; E. Rajh (My University, 2010)
The purpose of this research is to examine decision making styles and to test the Sproles and Kendall’s (1986) CSI instrument (Consumer Style Inventory) among young-adult consumers in the Republic of Macedonia. It segments young-adult consumers by their decision-making styles and determines the differences among segments relative to their decision-making styles. The empirical analysis is based on data obtained from consumer survey. The data were analyzed using Cronbach alpha coefficients, exploratory factor analysis and k-means cluster analysis. Research results confirmed eight-factor model. Two homogeneous segments of consumers were identified: Economic consumers and Recreational consumers. Significant gender differences were found on four factors of consumer-decision making styles (brand consciousness, novelty-fashion consciousness, recreational-hedonistic consumer and habitual, brand-loyal consumer). Marketing strategies should be tailored to the specific characteristics of consumers in the Republic of Macedonia.
Keywords: Consumer decision-making styles, Consumer Style Inventory, Consumer segmentation, Gender differences, The Republic of Macedonia